A review on the fabrication method of bio-sourced hybrid composites for aerospace and automotive applications - Zin, M. H.; Razzi, M. F.; Othman, S.; Liew, K.; Abdan, K.; Mazlan, N. (2016)
Development of bio-sourced materials over the recent years has shown growing interests due to their eco-friendly characteristics. The combination of bio-sourced material such as kenaf, jute, sisal and many more into current synthetic fibres such as glass and carbon fibre, which is also known as hybrid composites, offers several significant benefits including sustainability, cost reduction, product variety and high specific mechanical properties. There are many methods used to fabricate composite parts nowadays. However, each method has its own requirement and usability. This review paper intends to focus on suitable technique to be adopted in order to fabricate bio-sourced hybrid composites. Some of the fabrication methods are customized in order to suit with the application of natural fibres. The selected methods are also highlighted with the application in aerospace and automotive industry. The process and outcomes are presented comparatively.